1993
DOI: 10.1056/nejm199306103282303
|View full text |Cite
|
Sign up to set email alerts
|

Association between Exposure to Environmental Tobacco Smoke and Exacerbations of Asthma in Children

Abstract: Measurement of urine cotinine levels provides further evidence of an association between exposure to environmental tobacco smoke and pulmonary morbidity in children with asthma. These data emphasize the need for systematic, persistent efforts to stop the exposure of children with asthma to environmental tobacco smoke.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
187
3
13

Year Published

2003
2003
2011
2011

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 477 publications
(218 citation statements)
references
References 23 publications
13
187
3
13
Order By: Relevance
“…Multiple studies have reported that children exposed to ETS are at risk for developing lower lung function, increased use of rescue medications, and more frequent hospitalizations (15,16,31). As reported in RESULTS, averaged albuterol usage and LTE 4 levels were higher on days with higher cotinine levels but the effect of subsequent ambient pollutant concentrations was attenuated.…”
Section: Discussionmentioning
confidence: 81%
See 1 more Smart Citation
“…Multiple studies have reported that children exposed to ETS are at risk for developing lower lung function, increased use of rescue medications, and more frequent hospitalizations (15,16,31). As reported in RESULTS, averaged albuterol usage and LTE 4 levels were higher on days with higher cotinine levels but the effect of subsequent ambient pollutant concentrations was attenuated.…”
Section: Discussionmentioning
confidence: 81%
“…Almost all such studies estimate ambient health effects without taking into account concurrent exposures that may impact asthma, such as environmental tobacco smoke (ETS). However, in the setting of urban asthma, where high ambient exposures are assumed, concurrent exposures to ETS are also prevalent (13)(14)(15)(16)(17)(18)(19)(20). There are limited data on the response to ambient or indoor exposures in the typical urban environment where these concurrent exposures often occur.…”
mentioning
confidence: 99%
“…The CCR levels ranged from 0 to 1014 ng/ mg with an arithmetic mean of 85.03 ng/mg. Considering a limit of detection of 10 ng cotinine/mg creatinine (see Chilmonczyk et al, 1993), 30 (26%) of the 115 children children had no cotinine (27 children had 0 ng/mg and three children had between 0.5 and 0.7 ng/mg), whereas cotinine was detected in the other 85 (74%).…”
Section: Resultsmentioning
confidence: 99%
“…A 25-item questionnaire was developed from existing instruments (Chilmoncyzk et al, 1993;American Institute of Research, 1991;Asher et al, 1995;New York City Health and Hospitals Corp., 1995;Beckett et al, 1996;Koren, 1997;Eskenazi et al, 1999;Joseph et al, 1999) and was designed to characterize symptoms, health practices, and environmental exposure factors that have been documented to be asthma triggers or suspected asthma triggers (Chilmoncyzk et al, 1993;Ingram et al, 1995;Stoddard and Miller, 1995;Beckett et al, 1996;Koren, 1997;Platts-Mills and Carter, 1997;Eskenazi et al, 1999). Parents were requested to complete the questions (in either Spanish or English) about their child's respiratory health (symptoms, diagnosis, and medications), family history of asthma, school absenteeism, potential environmental exposures in the home, insurance status, and race/ethnicity.…”
Section: Methodsmentioning
confidence: 99%